Management of acute intermittent porphyria. (April 2014) - Harper, Pauline; Sardh, Eliane
<x xml:space="preserve">Abstract</x> Introduction: Acute intermittent porphyria (AIP) is characterized by acute neuropsychiatric and potentially life-threatening attacks precipitated by endogenous or environmental factors, such as reproductive hormones, fasting, stress, infection, certain porphyrinogenic drugs and alcohol, that is, factors requiring increased hepatic heme biosynthesis. Areas covered: This is a thorough review of the current knowledge regarding AIP (applicable to all the acute porphyrias), including pathogenesis of acute attacks and neurologic manifestations that fortunately only afflict a minority of carriers of potential disease-causing mutations of HMBS or other genes affecting heme biosynthesis. Prophylaxis and management measures of the acute attacks are covered and also recommendation of surveillance programs for possible late complications, such as systemic arterial hypertension, kidney disease and primary liver cancer (PLC). The strong evidence pointing to the liver as the central organ in the pathophysiology and amelioration of the clinical features of acute porphyrias is also covered. New possible forthcoming therapies are presented. Expert opinion: The natural history of AIP has importantly changed due to increased medical knowledge, laboratory diagnostic resources and the availability of human hemin for treatment of severe acute attacks. Liver transplantation is currently the utmost therapeutically curative alternative. Emerging genetic therapies for correction of hepatic heme biosynthesis are discussed. Emphasis on studying associated genes that modify vulnerability to develop acute attacks and PLC should become a priority, taking advantage of modern molecular technology and well-established networks.